Kebijakan Dividen terhadap Nilai Perusahaan pada Sektor Perbankan di Bursa Efek Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of dividend policy on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Using a quantitative approach, this research applies panel data regression with the Random Effect Model (REM) to measure the relationship between dividend policy (dividend payout ratio) as the independent variable and firm value (earnings per share) as the dependent variable. The research data were obtained from the annual financial reports of banks listed on the IDX during the observation period.This research employs a quantitative approach with a causal-associative method. Data were collected from the annual financial statements of banks listed on the IDX during 2020–2024. The analytical technique used was panel data regression with the Random Effect Model (REM) to test the direct effect of the independent variable, dividend policy, on the dependent variable, firm value.The results show that dividend policy has a positive and significant effect on firm value, meaning that the higher the dividend payout ratio, the higher the firm value as reflected in earnings per share. This finding implies that dividend policy can serve as a positive signal for investors in making investment decisions, as well as a reference for bank management in formulating optimal dividend policies.